Predicting the impact of the EU common agricultural policy reform in England: Micro and macroeconomic aspects - Areal, Francisco J.; Ceddia, Michele G.; Pazienza, Pasquale (Journal of Business Economics and Management, 2007)
In this article we investigate the effects of the European CAP reform on a selection of arable crops in England, both at a regional and national level. The results show that the CAP reform will push farmers to adjust to the new market conditions, which will cause a further restructuring of the English agricultural business sector. Our results show that, under the new market conditions, economically‐small farms will increase their output by allocating more land to cereals, whereas economically‐large farms will need to decrease land allocated to cereals to reduce production costs and achieve better returns. First Published Online: 14 Oct 2010